Guidelines and management of global risk: the European perspective - Hobbs, R (2004)
The anticipated rise in the prevalence of coronary heart disease (CHD) over forthcoming years throughout the world, including Europe, will place a significant burden on the healthcare system. Consequently, a major challenge that faces the medical profession is to improve the introduction of effective preventive strategies into routine clinical practice in order to blunt the scale of this epidemic. Current levels of risk factor management in patients with established cardiovascular disease are poor, and the implementation of primary preventive strategies to reduce the risk of cardiovascular morbidity and mortality in high-risk patients is even worse. The principal objective of clinical guidelines, such as those for the prevention of CHD issued by the Joint European Societies, is to improve the quality of patient care and health outcomes. However, the development of good guidelines by professional organizations does not guarantee their use in clinical practice. Surveys indicate that the most successful guidelines, in terms of implementation in general practice, are based on robust scientific evidence, are explicit in their recommendations, are uncontroversial, and demand minimal disruption to existing working procedures and workloads. © 2004 The European Society of Cardiology. Published by Elsevier Ltd. All rights reserved.